Wild Pedagogies and Young Children through the Mosaic Approach - A. Elizabeth Beattie; Sandra Scott; Douglas Adler (Australian Journal of Environmental Education)
This paper reports on a doctoral study that explored young children’s (ages 5 to 7 years) relationships with sticks during their school-based outdoor learning experiences. Sticks (parts of trees) became uniquely contextual agents due to the profound agentic effect the stick-based experiences, which were enacted through Wild Pedagogies, had on the children’s understandings of Place. Sticks were used in physical and symbolic ways throughout the children’s self-guided learning experiences. The children used long sticks to build large structures, houses, and other creations, and selected smaller sticks to represent microphones, brooms, or currency. The use of the Mosaic approach in this study aligns with Wild Pedagogies’ openness to new and different ways of being in and understanding the world, particularly as this approach privileges children, natural objects, and Place as agentic co-teachers and co-learners. The children demonstrated their agency as they made cognitive, physical, corporeal, agentic, affective, and aesthetic connections with Place, which they expressed through their Wild Pedagogical experiences. The study underscores the value of tactile, immersive, and bioregional experiences in helping children connect with nature, build knowledge, develop and share collective agency, and cultivate an ethic of care for the environment in Wild Pedagogical ways.